Increased plasma orexin-A concentrations are associated with the non-motor symptoms in Parkinson's disease patients. (10th January 2021) - Huang, Shen; Zhao, Zhenxiang; Ma, Jianjun; Hu, Shiyu; Li, Linyi; Wang, Zhidong; Sun, Wenhua; Shi, Xiaoxue; Li, Mingjian; Zheng, Jinhua
Highlights: The occurrence of Parkinson's disease is usually accompanied by hypothalamic damage. Orexin-A is produced by the hypothalamus and the periphery. Elevated plasma orexin-A levels were observed in early stages of Parkinson's disease. Plasma orexin-A levels may decrease with the progression of Parkinson's disease. Orexin-A plays an important role in non-motor symptoms of Parkinson's disease. Abstract: Background: Orexin, a neuropeptide primarily secreted by neurons in the lateral hypothalamus, has been implicated in Parkinson's disease (PD). Studies on the relationship between plasma orexin-A levels and PD are rare. Objectives: This study aimed to assess levels of plasma orexin-A in the progression of PD and to evaluate the correlation between orexin-A levels and non-motor symptoms. Methods: Enzyme-linked immunosorbent assay was used to determine plasma orexin-A levels in 117 healthy controls and 121 PD patients, including those with early (n = 68), medium (n = 40) and advanced (n = 13) stages of the disease. Evaluation of motor symptoms and non-motor symptoms in PD patients, such as sleep disorders, cognitive dysfunction, neuropsychiatric symptoms, autonomic nervous dysfunction, hyposmia and PD-related pain, were assessed by the associated scales. Results: Plasma orexin-A levels were significantly higher in PD patients compared to healthy controls. Orexin-A levels were elevated in early-stage and medium-stage PD compared to healthy controls, but were decreased in advanced-stage PD. Orexin-A levels were negatively correlated with the Unified Parkinson's Disease Rating Scale Part III scores, disease duration, and dopamine receptor agonist doses, and were positively correlated with the Pittsburgh Sleep Quality Index, REM-sleep Behavior Disorder Questionnaire, 14-item Hamilton Anxiety Scale, Mini-Mental State Examination, and Non-motor Symptom Scale items 22–24 scores. Conclusions: We found for the first time that plasma orexin-A levels were increased in early-stage and medium-stage PD and were decreased in advanced-stage PD. Furthermore, orexin-A levels were correlated with the non-motor symptoms of insomnia, REM-sleep behavior disorder, anxiety, cognitive dysfunction, and renal dysfunction.